2021
DOI: 10.1097/corr.0000000000002037
|View full text |Cite
|
Sign up to set email alerts
|

No Difference in Blood Loss and Risk of Transfusion Between Patients Treated with One or Two Doses of Intravenous Tranexamic Acid After Simultaneous Bilateral TKA

Abstract: Background Tranexamic acid (TXA) is often used to prevent excessive blood loss during bilateral TKA. Although it diminishes blood loss, TXA may have a potentially elevated thrombogenic risk with extra, unnecessary doses of TXA in this high-risk population. To date, the most efficacious dosing protocol in this setting has not yet been ascertained. Questions/purposes We compared one versus two doses of intravenous TXA in the setting of same-day bilateral TKA in terms of (1) perioperative blood loss that occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…Another study showed that sequential administration of oral TXA for up to 5 days after intravenous TXA did not decrease the hemoglobin drop after TKA 22 . Similar results with regard to the utility of single-dose intravenous TXA have been substantiated in simultaneous bilateral TKA to minimize excessive blood loss and reduce transfusions 23 . In the current economic landscape, administering multiple doses of TXA needs to show a substantial clinical benefit in order to consider such strategies, even using the oral route.…”
Section: Bleeding Control and Thromboprophylaxissupporting
confidence: 54%
“…Another study showed that sequential administration of oral TXA for up to 5 days after intravenous TXA did not decrease the hemoglobin drop after TKA 22 . Similar results with regard to the utility of single-dose intravenous TXA have been substantiated in simultaneous bilateral TKA to minimize excessive blood loss and reduce transfusions 23 . In the current economic landscape, administering multiple doses of TXA needs to show a substantial clinical benefit in order to consider such strategies, even using the oral route.…”
Section: Bleeding Control and Thromboprophylaxissupporting
confidence: 54%
“…In a systematic review and meta-analysis of TXA use in BTKA, He et al showed that intravenous TXA use significantly reduces blood loss and risk of blood transfusion, with no change in adverse effects such as rates of deep vein thrombosis (DVT) or pulmonary embolism 64 . Numerous other studies have supported the use of TXA in BTKA to reduce blood loss 67-69 .…”
Section: Current Guidelinesmentioning
confidence: 99%
“…Enter Wilde and colleagues [11], who found that when compared with a two-dose regimen, a single-dose regimen of intravenous TXA adequately prevented excessive blood loss and minimized the usage of blood transfusions in single-stage sequential bilateral TKA.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…A multiple-dosing regimen may be beneficial if the operation is longer than 4 hours. Wilde and colleagues [11] showed that a single-dose regimen of intravenous TXA was adequate to reduce the usage of blood transfusions in single-stage bilateral TKA. However, it is not known whether similar results can be reproduced in other centers, especially those with a lower TKA practice volume.…”
mentioning
confidence: 99%